Potential Molecular Mechanisms of Paederia Foetida L. In Gout Treatment Through Network Pharmacology And Molecular Docking - Tuan Hoang Quoc; Vy Hoang Ngoc Phuong; Thu Nguyen Thi Anh; Quynh Phan Le Nhu (The EuroBiotech Journal)
The global incidence of gout has been steadily increasing. Paederia foetida L., a traditional medicine, is used to treat gout in Vietnam, though its active compounds’ molecular mechanisms remain uncertain. This study used network pharmacology and molecular docking to predict the potential targets and pathways of P. foetida bioactive components in gout treatment, providing insights for clinical applications. Compounds and targets of P. foetida were identified using the TCMSP database, while targets associated with gout were obtained from GeneCards, TTD, and OMIM databases. A Venn diagram was employed to determine the common targets, and Cytoscape software was used to construct the compound-target-pathway interaction network. GO and KEGG enrichment analyses were performed to identify key biological processes and pathways. AutoDockTools was used to verify molecular docking between active compounds of P. foetida and core targets. Five active compounds and 49 common targets were identified. GO enrichment analysis revealed that P. foetida influenced multiple biological processes, cellular components, and molecular functions. KEGG analysis elucidated that the primary mechanism of P. foetida in gout treatment may be primarily related to the IL-17 signaling pathway and several other anti-inflammatories signaling pathways. Molecular docking confirmed strong binding (affinity < -5 kcal/mol) between five active compounds and core protein targets, including TP53, IL6, HSP90AA1, TNF, IL1B, BCL2, PTGS2, MAPK1, and MAPK8. Among the targets, the docking scores of MAPK8 (7.2-10.1 kcal/mol) were the best. Active compounds such as quercetin, beta-sitosterol, kaempferol, pelargonidin, and paederosidic acid methyl ester exhibited potential therapeutic effects on gout. Through in silico screening, the mechanism of action of P. foetida in treating gout can be determined to act on multiple targets through multiple pathways. This provides more ideas for in vitro and in vivo experiments to develop herbal medicines for gout treatment.